Reassessing Income Tax (PPh) Article 21 for MSMEs: An Islamic Economic Analysis of Justice, Maslahah, and Dharibah Principles - Mar'atusholihah, Rufaidah (Scimadly Publishing, 2025)
This study analyzes the compatibility of MSME taxation regulations with Islamic economic principles, identifies structural problems in tax collection, and proposes a reform model for MSME taxation that is just, educative, and inclusive. Using a qualitative approach with literature study, data were drawn from previous studies, scientific publications, and official government regulations, and analyzed through content analysis and narrative synthesis. The findings reveal a persistent gap between the current MSME final tax scheme and Islamic justice principles, as the tax burden often remains disproportionate to business capacity. Income Tax Articles 21 and 23 further create structural inequities by exerting greater pressure on MSMEs compared to larger taxpayers. Theoretically, this study contributes to the discourse on Islamic taxation by offering a conceptual framework that integrates progressive taxation with sharia-based justice, highlighting the importance of equity, proportionality, and inclusivity in tax policy design. Practically, the proposed reform model advocates adopting a progressive tax structure, enhancing tax literacy, and tailoring policies to the diversity of MSMEs while upholding sharia principles. The main limitation of this study is its exclusive reliance on literature review without empirical field validation.